Motivasi Penerjemahan Buku Berbahasa Arab - Abdul Munip (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2015)
The translation of Arabic books in Indonesia can’t be separated from some motives. At least, there are five motives of the translation, i.e. religious, educational, economic, ideological, and prevocational motives. Religious motive can be seen in the translator’s statements that his/her works are aimed to get a blessing from Allah. Educational motive can be seen in the fact that these works are aimed to give Islamic knowledge to the muslim community. Economical advantages are the most powerful motivations that publishers try to get by publishing Arabic translations books. In another hand, the ideological motive is one of the factors that the translators or publishers want to propagate their Islamic ideological among Indonesian Muslim community by mean of their translation works. Prevocational motive can be seen in translator intention to stimulate critical Islamic discourse in Indonesia by mean of translating Arabic books written by some Middle East critical writers.